Isolation and Purification of Chitosan Oligosaccharides (Mw ≤ 1000) and Their Protective Effect on Acute Liver Injury Caused by CCl4 - Kai Wang; Dawei Yu; Yan Bai; Hua Cao; Jiao Guo; Zhengquan Su (Marine Drugs, 2024)
Chitosan oligosaccharides are the degradation products of chitin obtained from the shell extracts of shrimps and crabs. Compared with chitosan, chitosan oligosaccharides have better solubility and a wider application range. In this study, high-molecular-weight chitosan oligosaccharides (COST, chitosan oligosaccharides, MW ≤ 1000) were isolated and purified by a GPC gel column, and the molecular weight range was further reduced to obtain high-purity and low-molecular-weight chitosan (COS46). Compared with COST, COS46 is better at inhibiting CCl4-induced cell death, improving cell morphology, reducing ALT content, and improving cell antioxidant capacity. The effects of COST and COS46 on CCl4-induced acute liver injury were further verified in mice. Both COS46 and COST improved the appearance of the liver induced by CCl4, decreased the levels of ALT and AST in serum, and decreased the oxidation/antioxidant index in the liver. From the liver pathological section, the effect of COS46 was better. In addition, some indicators of COS46 showed a dose-dependent effect. In conclusion, compared with COST, low-molecular-weight COS46 has better antioxidant capacity and a better therapeutic effect on CCl4-induced acute liver injury.